A Study of Theoretical Modeling for Scavenging Coefficients of Polydisperse Aerosols Removed by Rainfall - Xing Gao; Can Qi; Hongqiang Wang; Hui Zhu (Atmosphere, 2025)
This paper incorporates various currently known collection mechanisms (including Brownian diffusion, interception effect, inertial impaction, thermophoresis, diffusiophoresis, and electrostatic interaction) into the calculation of the total collection efficiency to analyze their impacts on the scavenging coefficient. The turbulent effect is introduced into the parametric study of the scavenging coefficient. Combining the local raindrop size distribution and aerosol size distribution, a theoretical prediction model for multi-fraction aerosol scavenging by rainfall is established and verified and corrected with measured data. The main conclusions are as follows: For particles within the accumulation mode range, the influence of the collision efficiency needs to be carefully considered. When studying the scavenging coefficient, it is necessary to combine the locally measured raindrop size distribution and aerosol size distribution. The influence of the aerosol size distribution on the scavenging coefficient under different seasonal conditions in the same area can be neglected. When the turbulent effect is introduced, the theoretical prediction is closer to the actual situation. In comparison with the actual measured PM2.5 values in Guangzhou City, Hefei City, and Tianjin City, the temporal variation characteristics of PM2.5 estimated by the theoretical model exhibit a substantial degree of consistency with the trends revealed by the measurement results. Additionally, a linear correlation is discernible between the scavenging coefficients obtained from field measurements in these three regions and those calculated by the theoretical model. Specifically, the equations of the linear relationships are Λs = 0.498 × 10−5 + 1.025Λm; Λs = 1.035Λm − 0.036 × 10−5; and Λs = 0.903Λm − 1.11 × 10−5.